Proceedings of the Ocean Drilling Program 1993
DOI: 10.2973/odp.proc.sr.130.047.1993
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Stratigraphy of the Ontong Java Plateau

Abstract: The Ontong Java Plateau, a large, deep-water carbonate plateau in the western equatorial Pacific, is an ideal location for studying responses of carbonate sedimentation to the effects of changing paleoceanographic conditions. These carbonate responses are often reflected in the physical properties of the sediment, which in turn control the appearance of seismic reflection profiles. Seismic stratigraphy analyses, correlating eight reflector horizons to each drill site, have been conducted in an attempt to map s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…These sequences continue to Site 289/586, and sequence mE has been interpreted at ODP Sites 807, 1183, and 1186. The sequences are laterally continuous and mostly parallel in water depths less than $2800 m; this relationship is consistent with observations from the northern and northeastern OJP Mosher et al, 1993]. In this region, seafloor topography largely reflects the morphology of the top of basement, despite the sediment and sedimentary rock column being >1000 m thick .…”
Section: Sedimentary Section Of the Main Ojpsupporting
confidence: 87%
See 1 more Smart Citation
“…These sequences continue to Site 289/586, and sequence mE has been interpreted at ODP Sites 807, 1183, and 1186. The sequences are laterally continuous and mostly parallel in water depths less than $2800 m; this relationship is consistent with observations from the northern and northeastern OJP Mosher et al, 1993]. In this region, seafloor topography largely reflects the morphology of the top of basement, despite the sediment and sedimentary rock column being >1000 m thick .…”
Section: Sedimentary Section Of the Main Ojpsupporting
confidence: 87%
“…Sediment and sedimentary rock characterized by reflections of low to high amplitude may be divided into three sequences: middle Miocene (mM), Miocene/Oligocene transition (M/O), and middle Eocene (mE) ( Figure 3). Similar high-amplitude reflections have been reported elsewhere on the OJP [e.g., Mosher et al, 1993]. At Site 806, near Site 289/586, synthetic seismograms were confined to the upper sedimentary section .…”
Section: Sedimentary Section Of the Main Ojpsupporting
confidence: 85%
“…The data are presented versus depth (above) and versus age (below). On the latter figures, the depth of the lysocline versus age are shown, as interpreted by Mosher et al (1993).…”
Section: Resultsmentioning
confidence: 99%
“…9. The data for Site 803 and Site 807 are plotted versus depth as well as versus age, the latter accompanied by a curve showing the interpreted level of the lysocline versus time (Mosher et al , 1993). The general level of intraparticle porosity is lower at Site 803 than at Site 807, corresponding to the results of Lind (1993b).…”
Section: Resultsmentioning
confidence: 99%
“…This carbonate low is expressed as a seismic reflector that can be traced over thousands of kilometers across the central equatorial Pacific (Mayer et al, , 1986. Mosher et al (1993) identified a reflector in the western equatorial Pacific that was tentatively correlated with this central equatorial reflector, and Bloomer et al (this volume) were able to link this central equatorial Pacific reflector with a similar reflector in the eastern equatorial Pacific, which they correlated with the 9.5-Ma "carbonate crash." Farrell et al (this volume) further explore the regional extent of the "carbonate crash" by rationalizing the age models and correlating the carbonate records (converted to mass accumulation rate) from a number of central equatorial Pacific sites (RC12-65, RC12-66, DSDP Site 574) with those from Leg 138.…”
Section: Middle/late Miocene Carbonate Transitionmentioning
confidence: 99%